Labor Market Dynamics in Urban China and the Role of the State Sector - Shuaizhang Feng; Naijia Guo (Institute of Labor Economics (IZA), 2019)
This paper studies the effect of state-owned enterprises on the dynamics of the Chinese urban labor market. Using longitudinal monthly panel data, we document very low dynamics in the labor market, especially in the state sector. We develop and calibrate an equilibrium search and matching model with three differences between the state and the non-state sector: labor productivity, labor adjustment cost, and workers' bargaining power. Counterfactual analysis shows that the lack of dynamics is mainly driven by the strong bargaining power of state-sector workers. Eliminating the differences between the two sectors substantially reduces the unemployment rate and long-term unemployment rate.
Keywords: J64; J45; P23; 330; state sector; labor market dynamics; search and matching; China; long-term unemployment